(untitled) (International Journal of Engineering and Computer Science, 2017)
“A thorough grounding in mathematics enhances educational and occupational opportunities for all people, whether sighted or visually impaired. In day-to-day routines, a practical understanding of mathematics allows a person to function more successfully and independently.” Access to, and doing mathematics, is one of the biggest obstacles for blind students in school and at the university. Our Braille Calculator will present new approaches to offering blind students better access to math, to provide new tools for doing math. In this report, the basic problems and solutions to the problem are discussed as a means of laying the groundwork for our Braille Calculator. Many aspects and concepts of mathematics are visual and spatial in nature. Students who are blind or visually impaired, and their teachers, now have standards which are closely aligned with those used for sighted students. Braille mathematics standards are essential to ensure that functionally blind students become literate in mathematics. However for complex engineering and statistical calculations even sighted students have to depend on Calculator. So we came up with an idea of Braille Calculator.